2013
DOI: 10.1155/2013/815621
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Antitumor Activity of Naturally Occurring Chalcones

Abstract: Chalcones, which have characteristic 1,3-diaryl-2-propen-1-one skeleton, are mainly produced in roots, rhizomes, heartwood, leaves, and seeds of genera Angelica, Sophora, Glycyrrhiza, Humulus, Scutellaria, Parartocarpus, Ficus, Dorstenia, Morus, Artocarpus, and so forth. They have become of interest in the research and development of natural antitumor agents over the past decades due to their broad range of mechanisms including anti-initiation, induction of apoptosis, antiproliferation, antimetastasis, antiang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 122 publications
2
39
0
Order By: Relevance
“…As an immunological agent from mulberry leaves, MLPs stimulate immunity and have anti-cancer properties. 5,[18][19][20][21] Early research data both in vitro and in vivo have proven that MLPs can increase both humoral and cellular immunity as evidenced by increased levels of antibody production and through the prevention of death in mice by bovine Pasteurella multocida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an immunological agent from mulberry leaves, MLPs stimulate immunity and have anti-cancer properties. 5,[18][19][20][21] Early research data both in vitro and in vivo have proven that MLPs can increase both humoral and cellular immunity as evidenced by increased levels of antibody production and through the prevention of death in mice by bovine Pasteurella multocida.…”
Section: Discussionmentioning
confidence: 99%
“…5,21,22 There were articles published previously on the induction of DC by many polysaccharides from plant resources and proved that these polysaccharides played immune enhancing role through DC driving. The results from these studies indicated that the polysaccharides could modulate the number of phagosomes and phagocytosis of DC, ACP activity of DC, expression of key surface co-signals molecules on DC and cytokines production by DC.…”
Section: Discussionmentioning
confidence: 99%
“…the anti-inflammatory, the antioxidant, the antiinfective (such as antileishmanial and antimalarial, and anti-tuberculosis), the antiviral, and above all the anticancer and antitumor activities of these compounds. The works of Ni et al (2004), Orlikova et al (2011), Sahu et al (2012 and Zhang et al (2013) are excellent reviews that shed light on the structure and mechanisms of action of chalcones with therapeutic properties. Actually, a number of chalcones have been successfully developed as commercial drugs for treatment of some digestive system diseases; and others are being clinically assayed for the treatment of cancer, cardiovascular diseases, and viral infections (Ni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Chalcone effects on tumor initiation, invasion and metastasis have been comprehensive reviewed by Orlikova et al (2011) and Zhang et al (2013). The antiproliferative activity of chalcones is due to their capacity to inhibit tubulin assembly and stop uncontrolled proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possess a wide range of pharmacologic properties, including antitumor effects (10)(11)(12). Because most dietary and synthetic polyphenols exhibit negligible toxicity even at relatively high concentrations, polyphenols are promising candidates for use in the development of novel anticancer drugs (13).…”
Section: Introductionmentioning
confidence: 99%